Using new media for citizen engagement and participation - Adrio, Marco L. 1959- (Advances in Public Policy and Administration (APPA) book series, 2020)
"This book explores the theoretical and practical aspects of how social media should be added to public-involvement activities such as citizen juries, public deliberation, and citizen panels"